Youth Subjectivities, Political Expressions and use of Digital Technologies - Bermúdez Grajales, Mónica María (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The present article accounts for conclusions derived from a document review carried out with the objective of inquiring into the relation between youth subjectivities, political expressions, and use of digital technologies. Both national and international scopes (Europe and the United States) were taken into account when revising 150 research papers published between 2000 and 2014. One of the main findings is that modern digital technologies engage high-impact political practices since they result in passionate, multimodal and incidental communications which get to depart from a traditional and representative policy in order to revolve around the desires and drives of contemporary youth subjectivities. It is further stated that the use of technologies is integrated into counterhegemonic proposals where the hypertext language appropriation constitutes the disidentification with a dominant logic. In that regard, videos, images, music, animations, links and text messages become the construction of a syntax that contributes to translate with a greater conviction emotions, affections and unrests at the present time.